1992
DOI: 10.1159/000126244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cortisol Infusion on the Pituitary-Adrenal Axis of the Hypothalamo-Pituitary-Disconnected Fetal Sheep

Abstract: In order to determine whether cortisol acts directly at the level of the fetal pituitary to promote pars distalis corticotroph maturation, we have infused cortisol into the hypothalamo-pituitary-disconnected (HPD) fetal sheep from 111 to 117 days of gestation. In this study we have measured fetal plasma cortisol and immunoreactive adrenocorticotrophic hormone (ir-ACTH) concentrations between 105 and 116 days of gestation, and we have determined the proportions of adult- and fetal-type corticotrophs in the pars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…On a molar basis, it shows 100% cross-reactivity with ovine ACTH-(1-39), human ACTH-(1-39), and ACTH- (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). It also reacts Ͼ90% with ACTH-(1-24) and Ͻ1% with ACTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) or human ACTH- . It does not crossreact with ACTH-(1-10), ACTH-(1-10) amide, ACTH-(4-11), ACTH- (11)(12)(13)(14)(15)(16)(17)(18)(19), ACTH-(11-24), or ACTH-(25-39) fragments of the ACTH-(1-39) peptide.…”
Section: Cell Immunoblottingmentioning
confidence: 99%
“…On a molar basis, it shows 100% cross-reactivity with ovine ACTH-(1-39), human ACTH-(1-39), and ACTH- (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). It also reacts Ͼ90% with ACTH-(1-24) and Ͻ1% with ACTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) or human ACTH- . It does not crossreact with ACTH-(1-10), ACTH-(1-10) amide, ACTH-(4-11), ACTH- (11)(12)(13)(14)(15)(16)(17)(18)(19), ACTH-(11-24), or ACTH-(25-39) fragments of the ACTH-(1-39) peptide.…”
Section: Cell Immunoblottingmentioning
confidence: 99%
“…An intact hypothalamic pituitary connection is essential, as clearly demonstrated by hypothalamic pituitary disconnection (HPD) studies in fetal sheep, in which the major consequences of this disruption are the absence of the cortisol surge (11,34,38,48,53) and delayed parturition (1,2,4,33). Increased adrenal responsiveness also is a critical mediating factor (18,21,41,51).…”
mentioning
confidence: 99%
“…We have reinvestigated this question using the more sophisticated technique of fetal H P D ( 3 ) in which the disconnection is made above the level of both the anterior hypophyseal arteries and long portal vessels, leaving the blood supply to the median eminence, pars tuberalis and pars distalis undisturbed (7). Previous studies with this preparation have shown that plasma ACTH concentrations in H P D fetuses, measured by radioimmunoassay, exceed those of controls before 135 days of gesta- tion after which intact fetuses exhibit an increase in ACTH (8)(9)(10). Elevated ACTH concentrations are also observed in adult sheep following HPD (11)(12)(13).…”
mentioning
confidence: 99%